Enhanced mechanical performance of additively manufactured PLA/TPU blend compatibilised with chain extender: a green material for sustainable aviation - Kahraman, Yusuf; Arvas, Melih Besir; Gumus, Omer Yunus; Arat, Refik; Ince, Ilyas; Yagci, Ozlem; Savas, Erhan (INDERSCIENCE ENTERPRISES LTD, 2026)
The aviation industry is actively pursuing the '2050 net zero goal' to mitigate petroleum-based fuel consumption and carbon emissions. A promising approach to achieving this target involves the use of sustainable aviation fuels, usage of bio-based materials and the adoption of lightweight components. This study explores the application of additive manufacturing (AM) to produce lightweight polylactide based parts for aircraft cabin interiors, which allows the creation of complex geometries in a cost-effective manner. Although flammability regulations present challenges for polylactide based components, small parts may qualify for exemption. We developed PLA/TPU blends, compatibilised with Joncryl 4468, using a twin-screw extruder and then produced filaments for 3D printing of small components in commercial airplanes. Mechanical and thermal properties of the additively manufactured blend samples were characterised in order to find an optimal formulation. An ecological and economic assessment demonstrated that this blend appears as a highly cost-effective and sustainable alternative.
Keywords: PLA; TPU; blend; aviation; cabin interior; additive manufacturing; AM; POLYLACTIC ACID; COST; Engineering